SOCIAL AND ECONOMIC IMPACT OF THE ERUPTION OF THE JORULLO VOLCANO (Tzintzun, Revista de Estudios Históricos, 2016)
In the second half of the seventeenth century in the Hacienda named Jorullo, owned by Joseph AndresPimentel, perpetual governor of the city of Patzcuaro, the Jorullo volcano erupted. This phenomenon ledto a strong economic and social impact that was manifested in economic and material losses from thedestruction of a significant portion of large estates and fields. The birth of the volcano also affected theentire population, especially to those who lost their homes and crops, forcing them to move. Some of themwent to neighboring towns like Churumuco and Tamacuaro because the damage caused by the volcanowas extensive. As a result of the consequent natural disaster, economic recovery in certain areas andhaciendas was very slow and so the landowners of the region used the eruption as a pretext for evadingthe payment of taxes to the Church and the Royal Treasury.
Keywords: Jorullo volcano; hacienda jorullo; natural disasters; social movility; La Huacana